2019
DOI: 10.1038/s41598-019-40018-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel RT-QPCR-based assay for the relative quantification of residue specific m6A RNA methylation

Abstract: N6-methyladenosine (m6A) is the most common and abundant RNA modification. Recent studies have shown its importance in the regulation of several biological processes, including the immune response, and different approaches have been developed in order to map and quantify m6A marks. However, site specific detection of m6A methylation has been technically challenging, and existing protocols are long and tedious and often involve next-generation sequencing. Here, we describe a simple RT-QPCR based approach for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Using online available m 6 A individual-nucleotide-resolution cross-linking and immunoprecipitation from HCT116 cells 27 we observed that the three m 6 A consensus motifs in the 5’UTR are methylated (see figure 1B ) and confirmed these results using an RT-qPCR-based method (see online supplemental figure 1E ). 28 In addition, taking advantage of the heterozygosity of the HCT116 cell line for the CD-associated SNP, we observed that the mRNA transcript carrying the CD-risk allele ( XPO1 *T) is more methylated than its alternative, protective form ( XPO1 *C) (see figure 1C ). As m 6 A methylation is involved in diverse RNA metabolic processes, we wanted to elucidate the effects of this differential methylation on the XPO1 mRNA.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Using online available m 6 A individual-nucleotide-resolution cross-linking and immunoprecipitation from HCT116 cells 27 we observed that the three m 6 A consensus motifs in the 5’UTR are methylated (see figure 1B ) and confirmed these results using an RT-qPCR-based method (see online supplemental figure 1E ). 28 In addition, taking advantage of the heterozygosity of the HCT116 cell line for the CD-associated SNP, we observed that the mRNA transcript carrying the CD-risk allele ( XPO1 *T) is more methylated than its alternative, protective form ( XPO1 *C) (see figure 1C ). As m 6 A methylation is involved in diverse RNA metabolic processes, we wanted to elucidate the effects of this differential methylation on the XPO1 mRNA.…”
Section: Resultsmentioning
confidence: 87%
“…Downloaded from Coeliac disease 1E). 28 In addition, taking advantage of the heterozygosity of the HCT116 cell line for the CD-associated SNP, we observed that the mRNA transcript carrying the CD-risk allele (XPO1*T) is more methylated than its alternative, protective form (XPO1*C) (see figure 1C). As m 6 A methylation is involved in diverse RNA metabolic processes, we wanted to elucidate the effects of this differential methylation on the XPO1 mRNA.…”
Section: The Cd-associated Xpo1 Allele Is Preferentially Methylated and Has Enhanced Translation Efficiencymentioning
confidence: 87%
“…Differentially methylated peaks between GF and CONV mice in the cecum were mainly linked to metabolism and immunological and inflammatory responses, functions known to be influenced by the microbiota. Additionally, changes in m 6 A modifications of specific transcripts have been linked to inflammatory intestinal disease in humans 34 , and also a T-cell specific conditional knock-out of Mettl3 led to intestinal inflammation in a mouse model 14 . Interestingly, we identified several risk genes for inflammatory bowel disease to be differentially methylated when comparing CONV and GF mice 64,65 , suggesting that microbiota-induced changes in m 6 A modifications might thus be linked to inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a complete understanding of mechanisms underlying gut-microbiota-host interactions still remains elusive. Recent reports have suggested that changes in m 6 A levels are associated with inflammatory states 14,34 and very recently, the presence of a microbiota has been suggested to induce changes in epitranscriptomic profiles in the brain, and several other tissues 35 .…”
mentioning
confidence: 99%
“…Several techniques, including untargeted epitranscriptomic sequencing methods, to measure m 6 A are available. Their strengths and weaknesses are listed in Supplementary Table S2 [ 20 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ]. First, the IHD-EPITRAN study plans to utilize, based on competitive tendering, one of the various mainstay second generation sequencing platforms for detecting the epitranscriptomically modified transcripts for initial insight [ 117 , 118 , 120 , 121 ].…”
Section: Methodsmentioning
confidence: 99%